Dynamic characteristics and crack evolution laws of coal and rock under split Hopkinson pressure bar impact loading. (1st July 2023) - Sun, Xiaoyuan; Jin, Tingxu; Li, Jihui; Xie, Jianlin; Li, Chuantian; Li, Xiaoxia
Abstract: The dynamic mechanical properties and crack evolution characteristics of coal and rock during split Hopkinson pressure bar (SHPB) impact failure are important contents for analysis. In previous studies, the coal and rock specimens used have usually been independent and not closely correlated. In addition, quantitative characterization and analysis methods for coal and rock cracks are immature, and more information has not been fully revealed. The aims of this paper are to comprehensively explore both the dynamic mechanical properties and crack evolution characteristics of coal and rock during impact failure. First, experimental specimens are prepared from coal seam, direct roof rock strata and direct floor rock strata in the same area to highlight the correlations between test pieces. Second, a dynamic strain gauge and high-speed (HS) camera are adopted to reflect the stress wave signal and crack evolution. Then, based on digital image correlation (DIC) technology and the mass screening method, the evolution laws of surface cracks during crushing and the distribution characteristics of sample fragments after crushing are studied from the perspective of fractal, and finally compared with those of the simulation analysis. The results are as follows. (1) The coal and rock samples from the same area have both consistency and differences. The dynamic mechanical properties of coal and rock are affected by the impact velocity and the physical properties of the specimen. Higher impact speeds and densities lead to the more obvious brittleness of the specimen when destroyed. Conversely, the sample shows more plasticity and ductile yield. (2) The self-similarity is significantly manifested in the evolution of surface cracks during impact and the distribution characteristics of fragments after impact. The box dimension and quality screening dimension are applicable to quantitatively characterize the evolution process and results of coal and rock fractures. (3) The simulation results based on the Holmquist–Johnson–Cook (HJC) and Riedel–Hiermaier–Thoma (RHT) constitutive models agree well with the experimental results, and the RHT constitutive model is more consistent. This study may contribute to a more comprehensive understanding of the dynamic characteristics and crack evolution laws of coal and rock under impact loading and provide references for further research and discussion.